Ventricular Septal Rupture after Acute Coronary Syndrome - Nascimento, Pedro Rafael de Oliveira; Góes, Gustavo Henrique Belarmino; Fabro, Caroline Bernardi; Sousa, Mateus Lopes Barreto de; Sepulveda, Diana Patricia Lamprea; Barros, Isly Maria Lucena de; Castillo, Jose Maria Del; Sousa Filho, José Breno de; Lima, Ricardo de Carvalho; Filho, Dário Celestino Sobral (International Journal of Innovative Research in Medical Science, 2019)
Objective: Ventricular septal rupture (VSR) is a rare but serious complication of acute myocardial infarction, which occurs in about 0.2 to 0.3% of patients with myocardial ischemia. If early therapy is not initiated, 90% of patients with VSR will die within the first month. This study aimed to evaluate the epidemiological and clinical characteristics of patients with VSR as a mechanical complication of acute myocardial infarction. Methods: A prospective study was conducted among nine patients who presented to the Cardiovascular Emergency Room of Pernambuco with acute coronary syndrome with ST segment elevation and VSR complications. Results: There were five women and 4 men, and the mean age of the patients was 72.5 years. The median time from the onset of the symptoms of acute coronary syndrome with ST segment elevation to the diagnosis of VSR was 3.5 days. Among the nine patients included in the study, three were treated surgically. Of all the patients, including those who underwent corrective surgery, eight patients died, 44.4% (N = 4), in the first four days after AMI. Conclusion: VSR occurs more frequently among elderly patients with multi-arterial involvement, lower wall infarction, and involvement of the right coronary artery. The prognosis is extremely limited, especially in patients who are already admitted to the cardiac emergency room with Killip IV, with > 24 hours of clinical evolution, and do not require surgical correction.